Chitrakar : the artist - Mukherjee, Binode Behari; Subramanyan, K.G. (Calcutta : Seagull Books, 2006)
Autobiographical reminiscences of Binod Behari Mukherjee, Indian painter; includes his aesthetic philosophy.
Glossary: p. 195-196
Keywords: Mukherjee, Binode Behari; Painters -- India -- Biography; Art -- Philosophy